The interplay of the aryl hydrocarbon receptor and β-catenin alters both AhR-dependent transcription and Wnt/β-catenin signaling in liver progenitors - Procházková, Jirina; Kabátková, Markéta; Bryja, Vítezslav; Umannová, Lenka; Bernatík, Ondrej; Kozubík, Alois; Machala, Miroslav; Vondrácek, Jan (Toxicological sciences, 2011)
β-catenin is a key integrator of cadherin-mediated cell-cell adhesion and transcriptional regulation through the Wnt/β-catenin pathway, which plays an important role in liver biology. Using a model of contact-inhibited liver progenitor cells, we examined the interactions of Wnt/β-catenin signaling with the aryl hydrocarbon receptor (AhR), a ligand-activated transcription factor, which mediates the toxicity of dioxin-like compounds, including their effects on development and hepatocarcinogenesis. We found that AhR and Wnt/β-catenin cooperated in the induction of AhR transcriptional targets, such as Cyp1a1 and Cyp1b1. However, simultaneously, the activation of AhR led to a decrease of dephosphorylated active β-catenin pool, as well as to hypophosphorylation of Dishevelled, participating in regulation of Wnt signaling. A sustained AhR activation by its model ligand, 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD), led to a downregulation of a number of Wnt/β-catenin pathway target genes. TCDD also induced a switch in cytokeratin expression, where downregulation of cytokeratins 14 and 19 was accompanied with an increased cytokeratin 8 expression. Together with a downregulation of additional markers associated with stem-like phenotype, this indicated that the AhR activation interfered with differentiation of liver progenitors. The downregulation of β-catenin was also related to a reduced cell adhesion, disruption of E-cadherin-mediated cell-cell junctions and an increased G1-S transition in liver progenitor cell line. In conclusion, although β-catenin augmented the expression of selected AhR target genes, the persistent AhR activation may lead to downregulation of Wnt/β-catenin signaling, thus altering differentiation and/or proliferative status of liver progenitor cells.
Keywords: Cytochrome P-450 CYP1A1; buněčné linie; proteiny Wnt; beta-katenin; Cell Adhesion; aromatické hydroxylasy; Cytochrome P-450 CYP1B1; hepatocyty; polychlorované dibenzodioxiny; Cell Line; Rats, Inbred F344; krysa rodu Rattus; Down-Regulation; cytochrom P-450 CYP1A1; down regulace; buněčná adheze; Hepatocytes; receptory aromatických uhlovodíků; kadheriny; potkani inbrední F344; buněčná diferenciace; Wnt Signaling Pathway; Receptors, Aryl Hydrocarbon; cytochrom P450 CYP1B1; Wnt Proteins; Cadherins; zvířata; játra; Liver; Rats; Animals; signální dráha Wnt; beta Catenin; Cell Differentiation; Polychlorinated Dibenzodioxins; Aryl Hydrocarbon Hydroxylases